PERANAN KULIAH KERJA NYATA SEBAGAI BAGIAN DARI PENGEMBANGAN KOMPETENSI MAHASISWA: Studi Kasus Mahasiswa Universitas Samudra KKN Tahun 2017 - Syardiansah Syardiansah (Universitas Putera Batam, 2019)
The Real Working Lecture (KKN) is a vehicle for the application and development of science and technology, which is conducted outside campus in time, working mechanism, and certain requirements. KKN implemented by the university is an effort to improve the content and weight of education for students and to gain greater added value in higher education. With the implementation of KKN is expected to develop social competence and student personality competence. The purpose of this study is to determine the role of Real Work Lecture as part of the development of student competence. Populations and samples in this study students participating KKN and community location student KKN implementation. Data collection methods used were interviews, observation, and documentation. Interview method aims to dig information about student's social competence and student's personality competence felt by society during KKN take place. From the research results obtained that the role of KKN as part of the development of student competence, especially social competence and personality competence is very clear found in the location of research.